(untitled) (Eurasian Medical Research Periodical, 2022)
The article says that the effectiveness of athletics largely depends on how much the teacher will pretend to be his planned plan, apply the most rational methods of organizing activities and methodological techniques, productively use the equipment, inventory, technical teaching aids, taking into account the places conducting classes, temperature conditions, preparedness of students, their age and individual characteristics. When organizing and conducting athletics classes, it is especially important to ensure their safety. Be sure to instruct students on safety